2021
DOI: 10.1002/casp.2500
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in children in the aftermath of disasters: A systematic review and a new perspective on individual, interpersonal, group, and intergroup level factors

Abstract: Disasters can impact upon individuals, families, and communities in multiple ways. Research has mainly focused on risk and protective factors relating to the child (individual level) and the family (interpersonal level), not taking into account the processes at the level of social groups. The present review aims to (a) review psychological research on disasters determined by natural events in childhood, (b) distinguish individual, interpersonal, group, and intergroup levels, (c) emphasize the importance of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 103 publications
(159 reference statements)
0
17
0
Order By: Relevance
“…Emergency situations are intrinsically uncertain, with an array of possible impacts on victims and their living conditions, livelihood, health and in the most extreme conditions, life itself. They have consequences on an individual level, as well as on an interpersonal, group, and intergroup level, making the question of prosocial actions amongst individuals, both children and adults, all the more essential in these contexts (Cadamuro et al, 2021). Despite individual danger including the risk of losing one's life, prosocial behaviors are observed in many different emergency situations (e.g., natural disasters, wars, terror attacks…) regardless of their timeframe, location and outcome, although they do not give rise to one single type of behavior.…”
Section: Discussion and Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency situations are intrinsically uncertain, with an array of possible impacts on victims and their living conditions, livelihood, health and in the most extreme conditions, life itself. They have consequences on an individual level, as well as on an interpersonal, group, and intergroup level, making the question of prosocial actions amongst individuals, both children and adults, all the more essential in these contexts (Cadamuro et al, 2021). Despite individual danger including the risk of losing one's life, prosocial behaviors are observed in many different emergency situations (e.g., natural disasters, wars, terror attacks…) regardless of their timeframe, location and outcome, although they do not give rise to one single type of behavior.…”
Section: Discussion and Methodological Considerationsmentioning
confidence: 99%
“…Protective factors can buffer the psychological impact of exposure to emergencies and related secondary adversities (Fegert et al, 2020;Masten & Narayan, 2012;Pfefferbaum et al, 2015). Individual-level as well as collective-level factors interact to promote resilience following a disasters (Cadamuro et al, 2021). Peer and caregiver support, adaptive coping, emotion regulation, perceived sense of control, self-esteem, and prosocial behaviors have all been associated with lower psychopathology after an emergency (Fegert et al, 2020;Lengua et al, 2005;Lewis et al, 2015;Masten & Narayan, 2012;Pfefferbaum et al, 2015).…”
Section: Emergency Situations and Their Impact On Children From Psychological Consequences To Prosocial Behaviormentioning
confidence: 99%
“…Studies have also looked at the psychological consequences of sudden social and natural disasters on people's distress levels and behavioral changes, and researchers have investigated factors that influence adaptation and resilience, such as attachment, intelligence, behavioral regulation, and community systems (Masten & Obradovìc, 2008). Researchers have also studied how different factors on the individual level (e.g., age, gender, ethnicity, mental health, cognitive skills), and interpersonal and intergroup levels (e.g., social support, social status, intergroup conflict) influence the impact of change on our lives and affect our resources for adaptation (Cadamuro et al, 2021). The broader social, political, and economic factors that affect individual lives have also been taken up, especially within such social theories as Durkheim's classic study on suicide (1897/1951) and more recent research such as Rosa's (2013) work on social acceleration.…”
Section: Understanding the Self Through Changementioning
confidence: 99%
“…Consequently, people will respond with such behaviour (and be most open to risk communication) that corresponds to their normative understanding of what constitutes an appropriate response. At the same time, a large body of research on crowd behaviour demonstrated that the collective experience of disaster can translate into a social identity, hence, leading people to think and act as an interdependent entity rather than as independent individuals (Cadamuro et al, 2021; Drury et al, 2009). In sum, one may expect that risk communication that focuses on independent responses falls short in addressing people with an interdependent self‐construal tendency and vice versa.…”
Section: Introductionmentioning
confidence: 99%